PENGUATAN PENDIDIKAN DAN EKONOMI KELUARGA BAGI JAMA’AH TIDAK MAMPU DI MASJID AL-JIHAD BANJARMASIN PERSPEKTIF MAQÂSHID ASY-SYARÎ’AH - Norcahyono, Norcahyono; Rusina, Yenni (FIKRUNA: Jurnal Ilmiah Kependidikan dan Kemasyarakatan, 2024)
Article is motivated by the "Al-Jihad Cares" program owned by the Al-Jihad Mosque, Muhammadiyah Branch 4, Banjarma sin. The "Al-Jihad Cares" program is very interesting, because this program has great potential as a solution in helping congregations who are unable to fulfill and improve basic needs in strengthening an independent family. The method used in this research is descriptive-analytic with an Islamic legal philosophy approach. The analysis technique is to describe the research results based on the problems being studied, then analyze them using an Islamic legal philosophy approach, in this case Maqâshid asy-Syarî'ah . Among the Banjarmasin Mosque al -Jihad programs which are oriented towards strengthening congregation who do not capable is a strengthening program education for family the congregation does not capable. this program implemented in effort help congregation who have the kids will separated school , help And motivating they For Spirit demand knowledge to become an educated , moral generation And character . In review Maqâshid ash-Shari'ah this program is an emergency program in maintaining religion and sense. As for the strengthening program economy family for congregation who do not capable implemented with pattern give a number Money cash every month , give Money cash for additional capital business scale small or as initial capital For open business home . In perspective Maqâshid ash- Shari'ah program This is emergency matter​ in strive need basic life​ in A family. Based on findings results research , Takmir Mosque has not provided a sustainable evaluation , because There is no special monitoring and assistance yet to achievements of the "Al-Jihad Cares" program , and matter even this recognized by they.